(untitled) (Revista Direito em Debate, 2021)
The article proposes an inquiry into International Security and the current position of subtracting human rights guarantees already consolidated at the international level. Our questioning continues to speculate about the real need to feel secure, we must give uprights. Thus, we expose the principles of International Security and religious freedom, invoking past events as national laws that prevent the use of religious artifacts in the public and public use of national believers in the name of greater security. Still, we wonder about what will come next: which of the freedoms will be placed in the limelight, how much of a bargain will we have between rights and security? To do so, we will make a list of considerations that begin with identifying what is international security, what is the common threat to the world, and what freedoms are visibly attained so far.